The VALIDATE handbook : an approach on the integration of values in doing assessments of health technologies - Oortwijn, W. J.; Sampietro-Colom, Laura (Radboud University Press, 2022)
Health Technology Assessment (HTA) is defined as a multidisciplinary process that uses explicit methods to determine the value of a health technology at different points in its lifecycle. The purpose is to inform decision-making in order to promote an equitable, efficient, and high-quality health system. The definition reflects that facts and values are intertwined in HTA. This means that HTA should be considered as a type of policy analysis, wherein the assessment of safety, clinical and cost implications of health technologies, as well as their wider ethical, legal, social, organizational, environmental and other implications is conducted from the view that these aspects are closely interrelated, and wherein stakeholders are involved in a more productive way throughout the process of HTA. Acknowledging this holds the potential of conducting assessments of health technologies in a way that supports deliberative democratic decision making. In the 2018-2021 EU Erasmus+ strategic partnerships project "VALues In Doing Assessments ofhealthcare TEchnologies" (VALIDATE), a consortium of seven academic and HTA organizations have developed an approach to HTA that allows for the integration of empirical analysis and normative inquiry. 'The VALIDATE handbook: an approach on the integration of values in doing assessments of health technologies' offers the reader an opportunity to get acquainted with the theoretical considerations and apprehend the associated practical and organizational implications of this approach. It offers those interested in HTA to integrate empirical analysis and normative inquiry in a transparent way.